Reliability and Validity of the L Test in Persons With Multiple Sclerosis - Bilek, Furkan; Demir, Caner F. (Sage Publications Inc, 2025)
The L Test has been developed to assess balance and gait disorders. Our aim in this study was to estimate the test-retest reliability and validity of the L Test when used with 82 persons with multiple sclerosis (PwMS). For these participants, we examined the degree of agreement between the results of a first and second administration of the L Test (separated by one day), using Bland-Altman analysis and intra-class correlation coefficients (ICCs). We computed minimal detectable change (MDC) and standard error of measurement (SEM) values for the L Test and evaluated concurrent validity by correlating L Test results with the Timed Up and Go test (TUG) and the 10-minute Walk Test (10MWT). Prior to administering these measurements, we randomized the sequence of the test administrations to our participants. The Bland-Altman analysis showed that L Test was reproducible, with upper and lower limits of agreement of 0.99 and -1.45 seconds, respectively. The L Test demonstrated excellent test-retest reliability, with an ICC value of 0.996 (95% CI: 0.994-0.998). Cronbach's alpha coefficient was 0.996. The performance of the L Test is measured by seconds required to complete the task, and we found the L Test SEM value to be 0.35 seconds, and its MDC value to be 0.97 seconds. The L Test showed a strong correlation with both the TUG test (rho = 0.936; p < .001) and the 10MWT (rho = 0.925; p < .001). We concluded that the L Test is a reliable and valid \ tool for assessing functional mobility and balance in PwMS.
Keywords: multiple sclerosis; L Test; gait; balance; reliability; validity